Synthesis and Characterization of Zinc Oxide Nanoparticles with Small Particle Size Distribution - Nuraqeelah, Mohammad Shamhari; Boon, Siong Wee; Chin, Suk Fun; Kuan, Ying Kok (Slovenian Chemical Society (Slovenia), 2018)
Solvothermal synthesis has shown to have a great potential to synthesize Zinc Oxide nanoparticles (ZnO NPs) with less than 10 nm size. In this study, we present a rapid synthesis of ZnO NPs in which ZnO NPs with more uniform shape and highly dispersed were synthesized using zinc acetate dihydrate (Zn(CH3COO)2 2H2O) and potassium hydroxide (KOH) as a precursor and absolute ethanol as solvent via solvothermal method. Few techniques were exploited to characterize synthesized ZnO NPs including X-ray diffraction (XRD), transmission electron microscope (TEM), Brunauer-Emmett-Teller (BET), energy-dispersive X-ray spectroscopy (EDX), fourier transform infrared (FT-IR) spectroscopy, and ultraviolet visible (UV-Vis) spectroscopy. Synthesized ZnO NPs that were prepared via solvothermal synthesis method at 60 °C for 3 hours exhibited a wurtzite structure with a crystalline size of 10.08 nm and particle size of 7.4 ± 1.2 nm. The UV-vis absorption spectrum has shown peak at 357 nm indicate the presence of ZnO NPs. Hence, better quality with uniform size ZnO NPs can be easily synthesized with reduced amount of time via solvothermal synthesis method rather than using other complicated and lengthy synthesis methods.